Anatomy of Fibre Bundles (Filaments) Determines the Yield and Quality of Bast and Leaf Fibres - Maiti, Ratikanta (International Journal of Economic Plants, 2017)
The paper makes a concise review of research undertaken on anatomy of bast and leaf fibres and its possible relation with yield and quality. The results show a large variability in different anatomical traits among different species and also among genotypes of the same species. In view of the facts that breeders have no direct selection criteria for breeding for yield and quality, the author suggests that this is a potential line of research to use anatomical traits of the bast fibres as selection criteria for possible genetic improvement for yield and quality.